2020
DOI: 10.1136/oemed-2020-106459
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring among emergency medical services night shift workers

Abstract: ObjectivesHigher 24-hour blood pressure (BP) and blunted BP dipping during sleep and night-time hours are associated with adverse health outcomes. Night shift work may affect 24-hour BP and dipping patterns, but empirical data in emergency medical services (EMS) clinician shift workers are sparse. We implemented ambulatory blood pressure monitoring (ABPM) in EMS workers to characterise BP during night shift work versus a non-workday, and sleep versus wake.MethodsParticipants worked night shifts. Hourly ABPM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…112,[154][155][156] Naps may facilitate adaptation to a shift work schedule and ease the return to daytime activity, 157,158 and may offer cardiovascular health benefits. 159,160 Split sleep schedules, in which a person takes a nap after a work shift and another nap before the next shift, have been associated with increased sleepiness, 161 but few differences in performance relative to a consolidated post-shift sleep bout. 162,163 For on-the-job napping to be implemented successfully as a countermeasure strategy, it is important that it be sanctioned 164 and that there is access to a safe and quiet place to rest while on break.…”
Section: D2 Nappingmentioning
confidence: 99%
“…112,[154][155][156] Naps may facilitate adaptation to a shift work schedule and ease the return to daytime activity, 157,158 and may offer cardiovascular health benefits. 159,160 Split sleep schedules, in which a person takes a nap after a work shift and another nap before the next shift, have been associated with increased sleepiness, 161 but few differences in performance relative to a consolidated post-shift sleep bout. 162,163 For on-the-job napping to be implemented successfully as a countermeasure strategy, it is important that it be sanctioned 164 and that there is access to a safe and quiet place to rest while on break.…”
Section: D2 Nappingmentioning
confidence: 99%
“…The presence of BP nondipping in healthy individuals is, therefore, not only a risk factor for future CVD but also an important warning sign of future CVD risk. There is some evidence that sleep quality and sleep efficiency may be associated with nocturnal BP nondipping in otherwise healthy individuals, however, the studies reporting on this were limited and further studies are required [49,50,56].…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, the implications of circadian misalignment between the biological clock and the sleep/wake cycle are well known [83] and it is well recognized that shift work has a negative impact on health, specifically that shift workers are already at a higher risk of developing hypertension [83–85]. Of the three studies reporting on shift workers [50,52,57] all showed that shift workers displayed BP nondipping during sleep on nonshift days. One might speculate that the fact that shift workers display BP nondipping during sleep on nonshift days may, at least in part, be related to chronic circadian misalignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations